POTENTIALITY LOCAL HEALTHLITERACY IN SUAN PHUENG DISTRICT, RATCHABURI PROVINCE - Sunyamo, Thararat; Nilkote, Reongwit; Rueangsri, Wongsiri; Lundam, Chatree; Chaiprapathong, Surachet (Journal of Social Science and Cultural, 2021)
The objective of this article were to: 1) study the process of driving local health literacy of Suan Phueng district, Ratchaburi province, and 2) Provide guideline for potentiality local health literacy to develop health literacy. This was qualitative research that studies data from documents, in-depth interviews, group discussions and taking lessons. The key informants include 1) leaders for 15 persons, 2) local community members for 15 persons, and 3) community-related partners for 15 persons, total of 45 persons. By selected purposive sampling, content analysis data, and summarized overall. The research was found that: 1) process of driving local health literacy have 4 approaches include 1.1) context of the area and supporting factors, 1.2) local governance and the local population, 1.3) local health literacy paradigm, and 1.4) lessons of empowering local communities in driving health literacy. Therefore, the creation of good health must cover both the physical dimension, the mental dimension, the social dimension, the intellectual dimension. The process is the integration of skills, strategies, and information seeking for good health. And 2) Provide guideline for potentiality local health literacy to develop have 5 aspects include 2.1) understand and learn the situation and context of the area, 2.2) people are the center of driving work, 2.3) partnership management, 2.4) to create the learning process, and 2.5) propose for common goals. Therefore, the potentiality of health literacy requires a focus on local capacity. meet the needs contextual necessity and perform appropriately This will lead to a sustainable drive to promote health.